(untitled) (Bangladesh Journal of Scientific and Industrial Research, 2011)
A protocol was established for mass clonal propagation of Phalaenopsis amabilis cv. ’Golden horizon’ through in vitro culture of young leaf segments from mature plant. Explants were cultured on half strength Murashige and Skoog (1/2 MS) medium supplemented with N6-benzyladenine (2.0 mg l-1), a-naphthaleneaceetic acid (0.5 mg l-1), 2% (w/v) sucrose, 10% (v/v) coconut water, 2 g l-1 peptone and 1 g l-1 activated charcoal. Each section of explant produced 15 protocorm-like bodies (PLBs) after 12 weeks of culture. When phytohormone was omitted from the medium and 150 mg l-1 L-glutamone was added PLBs were found to be enlarged with leafy shoots and new PLBs were induced from the base of the old ones. Leafy shoots rooted on half strength MS medium supplemented with 2 g l-1 peptone, 2% (w/v) sucrose, 10% (v/v) CW and 1 g l-1 activated charcoal, where 100% explants were developed into plantlets with roots within 8 weeks. The addition of 2.5 g l-1 banana pulp powder enhanced the number and length of roots. Within the first 32 weeks after initiation of culture about 1500 plantlets as well as a huge amount of PLBs were achieved from a single explant section. The plantlets were acclimatized in natural environment. Key words: Phalaenopsis orchid; Leaf segments; Protocorm-like bodies; Micropropagation DOI: http://dx.doi.org/10.3329/bjsir.v46i2.8182 Bangladesh J. Sci. Ind. Res. 46(2), 163-168, 2011